Chứng minh \(f\left(x\right)=x^{50}+x^{49}+x^{48}+....+x^2+x+1\) chia hết cho
\(g\left(x\right)=x^{16}+x^{15}+....+x^2+x+1\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x2 - 2x + 4 - x2 - 9 = 6
- 2x - 5 = 6
-2x = 11
x= \(-\frac{11}{2}\)
(x-2)2-(x-3)(x+3)=6
x2-4x+4-(x2-9)=6
x2-4x+4-x2+9=6
-4x+13=6
-4x=6-13
-4x=-7
x=(-7):(-4)
x=7/4
\(\left(2x-1\right)\left(x-5\right)-x^2+10x-25=0\)
\(\left(2x-1\right)\left(x-5\right)-\left(x^2-10x+25\right)=0\)
\(\left(2x-1\right)\left(x-5\right)-\left(x-5\right)^2=0\)
\(\left(x-5\right)\left(2x-1-x+5\right)=0\)
\(\left(x-5\right)\left(x+4\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-5=0\\x+4=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=5\\x=-4\end{cases}}\)
Vậy \(\orbr{\begin{cases}x=5\\x=-4\end{cases}}\)
\(\left(5n-3\right)^2-9=\left(5n-3\right)^2-3^2=\left(5n-3-3\right)\left(5n-3+3\right)=5n\left(5n-6\right)\)
Ta có: \(5⋮5\)
\(\Rightarrow5n\left(5n-6\right)⋮5\forall n\in Z\)
\(\Rightarrow\left(5n-3\right)^2-9⋮5\forall n\in Z\)
đpcm
F(x) = ( x^50 + x^49 + ....+ x^34) + ( x^33 + x^ 32 +...+ x^17) + ( x^16 + x^15+...+ 1)
= x^34 ( x^16 + x^15 +...+1) +x^17( x^16 + x^15+...+ 1) + (x^16+...+1)
=(x^16 + ....+ 1)(x^34 + x^17+ 1) chia hết cho ( x^16 + x^15 + ...+1)
Hay F(x) chia het cho G(x)